Chromosome 7 Deletion and Its Role in Nephrocalcinosis: A Study in an Iraqi Family: Association of chromosome 7 with nephrocalsinosis - Asmaa Amer Almukhtar (Iraqi Journal of Cancer and Medical Genetics, 2024)
Background: Nephrocalcinosis refers to medulla calcium phosphate deposition in the kidney. It can occur as a result of some diseases, drugs, or physiological or genetic effects. Genetic effects can involve either genes or chromosomal disorders. Nephrocalcinosis was thought to be not inherited condition. Objective: A family of six members who were suffering from nephrocalcinosis were referred to the Iraqi Center for Cancer and Medical Genetics for chromosomal analysis. Methods: G-banding chromosomal analysis was performed according to the ICCMGR protocol, karyotype analysis was performed via CytoVision (Leica Microsystems Crop), and chromosomal nomenclature was designated according to ISCN 2020. The aim of this study was to report the role of the deletion of region 7p22 associated with nephrocalcinosis. Results: The relatives exhibited breaks at the common fragile site 7p22, some of which were chromatid breaks and others chromosomal deletions. Few cells within adult samples presented chromosomal abnormalities extending to the 7p21 band. To our knowledge, the correlation between fragile site 7p22 and nephrocalcinosis has not been previously reported, as we have shown in our present study. Only two previous studies mentioned the role of the association between aldosterone and 7p22, and the other study mentioned the association between aldosterone and nephrocalcinosis; thus, our current study clarifies a new relationship between 7p22 and nephrocalcinosis, especially when we know that the region holds some genes involved in renal genesis and kidney function. Our conclusion is that the region 7p22-ter holds effective genes involved in kidney function, and its deletion may lead to the appearance of nephrocalcinosis, and the fragile site 7p22 may play a role in nephrocalcinosis.